ENERGY AND COSTS SAVING AIR CONDITIONING SYSTEM OF SHOPPING MALL BUILDINGS: A CASE STUDY IN JAKARTA - Agus Marjianto; Haftirman Haftirman (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2021)
The air conditioning system for the Mall A building in Jakarta uses a central air conditioning system with a constant flow chiller with TES (Thermal Energy Storage). This system will be verified by measuring data regarding cooling load of the Mall A. The peak cooling load measurement results is 12,299 kW with a total cooling load of 45,733,180 kWh for 1 year. The result of the measurement data will be compared to cooling load calculation by Trace 700 software. Based on Trace 700 software, the peak cooling load is 12,594 kW with a total cooling load of 44,617,405 kWh. Furthermore, using the actual measurement data of the air conditioning system in Mall A, it will be compared with a central air conditioning system with a magnetic bearing chiller which will be equipped with VSD (Variable Speed Drive) to find out how well its energy performance and costs are for a mall building similar to Mall A, as a potential for energy and cost savings. The results of energy calculations and cost analysis, the central air conditioning system with the magnetic bearing chiller is 99 kWh/(m2.year) and the life cycle costs for 20 years, 30 years, and 50 years are 339,828,248,242 IDR, 415,994,136,400 IDR, 521,915,598,761 IDR. While the results of energy calculations and cost analysis, the TES combination constant flow chiller central air conditioning system is 141 kWh/(m2.year) and the life cycle costs for 20 years, 30 years, and 50 years are 435,150,140,059 IDR, 541,700,386,487 IDR, 690,535,151,478 IDR. Based on the foregoing, the central air conditioning system with variable flow magnetic bearing chiller is a better system than the central air conditioning system with TES combination constant flow chiller for shopping mall buildings similar to Mall A.